2019
DOI: 10.1016/j.healthplace.2019.102153
|View full text |Cite
|
Sign up to set email alerts
|

The role of the physical environment in adolescent mental health

Abstract: The existing literature suggests an association between the physical environment and mental health but also complex relationships between the social and the physical environment as well as between objective and subjective measures of the environment. In this study, we attempted to explore the role of the residential neighbourhood's physical environment in adolescent mental health, taking this complexity into account. Using data on 3683 ten-to 15year-olds from England and Wales who participated in Understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 51 publications
4
23
1
Order By: Relevance
“…Our findings further corroborate previous studies that have documented discordant results between subjective and objective neighborhood measures and health outcomes. This emphasizes the importance of personal observations of daily environments and supports the rational for including both subjective and objective measures in study designs [50, 51, 71].…”
Section: Discussionmentioning
confidence: 84%
“…Our findings further corroborate previous studies that have documented discordant results between subjective and objective neighborhood measures and health outcomes. This emphasizes the importance of personal observations of daily environments and supports the rational for including both subjective and objective measures in study designs [50, 51, 71].…”
Section: Discussionmentioning
confidence: 84%
“…The remaining studies predominantly showed beneficial relationships between green space and depression, emotional well-being and mental health and behaviour. One study showed a beneficial association between green space and depression reduction [ 51 ], one between green space and emotional well-being [ 29 ], one with mental health and behaviour (using the strengths and difficulties questionnaire; SDQ) [ 52 ]; however, three showed a non-significant relationship [ 53 , 54 , 55 ]. A further study reported a positive association between green space and reduced risk of serious psychological distress [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five cross-sectional studies examined associations between neighbourhood greenness and adolescents’ mental well-being. Two of the five studies quantified greenness as the percentage of green space for each postal code area or UK ward in the adolescents’ residential area [ 33 , 55 ], and three used a Normalized Difference Vegetation Index (NDVI) derived from satellite images in buffers of 250–1250 m, 250–950 m or 500 m around the residential addresses of participants [ 49 , 51 , 56 ]. One study measured the percentage of green space within each 5 km radius circular buffer in school settings [ 54 ], and another used neighbourhood park access by measuring the area of park land divided by total land within 0.80 km distance (along street networks) of a participant’s home [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations